Binder composition for fuel cell and preparation method thereof
By using a hot melt adhesive layer of acid-modified polyolefin resin and modified polyurethane resin in the fuel cell, a high-performance adhesive composition is formed, which solves the problem of insufficient sealing between the bipolar plate and the membrane electrode of the fuel cell, and improves the service life and production efficiency of the stack.
Patent Information
- Application Number
- CN202411700228.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The sealing between the existing fuel cell bipolar plate and membrane electrode is insufficient, resulting in the risk of gas mixing, leakage and safety accidents. The assembly is complicated and unassembled positions are prone to occur, reducing the overall sealing performance.
Using a fuel cell adhesive composition, including an acid-modified polyolefin resin hot melt adhesive layer and a modified polyurethane resin hot melt adhesive layer, the adhesive product with high cohesion strength, hydrolysis resistance and cold and heat impact resistance is formed through hot melt bonding technology.
It improves the simplicity and efficiency of the single cell production process, enhances the bonding strength between the bipolar plate and the membrane electrode, solves the durability problem of the components in a moisture-contact environment, extends the service life of the stack, and reduces production costs.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fuel cells, and in particular to an adhesive composition for fuel cells and a preparation method thereof. Background Art
[0002] A fuel cell is a highly efficient power generation device that converts the chemical energy in fuel and oxidant directly into electrical energy. As the "heart" of a hydrogen fuel cell vehicle, the long-term stability and service life of the stack are crucial. If the entire stack system is to operate effectively and for a long time in a closed environment, good sealing is required.
[0003] Proton exchange membrane fuel cells use perfluorosulfonic acid proton membrane as electrolyte, and its core component is membrane electrode (MEA for short), which is mainly composed of proton exchange membrane, cathode / anode catalyst layer and cathode / anode gas diffusion layer. As another core component of fuel cells, metal bipolar plates have become a new choice after graphite bipolar plates due to their high thermal conductivity, high air tightness, high Young's modulus and good manufacturing process. Since oxidants and fuels need to be introduced into both sides of the fuel cell respectively, permeability becomes an important parameter to characterize battery life. If the permeability between the bipolar plate and the membrane electrode is large, the fuel and oxidant will mix during use, which will not only reduce the power generation efficiency of the fuel cell, but also may cause serious safety accidents. Therefore, in order to prevent gas mixing, gas and refrigerant leakage, the sealing between the fuel cell bipolar plate and the membrane electrode must be strictly controlled.
[0004] At present, the main sealing methods between bipolar plates and membrane electrodes on the market are sealing rings, glue injection and laser welding. Although these packaging methods can basically meet the sealing requirements, they still have the following disadvantages: the existing technical solutions will design corresponding rubber sealing rings to play the corresponding sealing role, but as the number of single battery cells in the battery stack increases, this sealing ring structure will make the assembly process very complicated, and it is easy to have unassembled positions, reducing the overall sealing performance of the battery stack; after the bipolar plate is completed by laser welding, the residual stress will cause the bipolar plate to bend and deform after the clamp is removed, causing difficulties for the subsequent stacking process; the sealant on the surface of the bipolar plate or membrane electrode can only stick to a certain surface after hot pressing, and cannot fully bond the components on both sides. Therefore, during the operation of the battery, the gas on both sides of the anode and cathode may enter the other side through one side of the two components, thereby increasing the permeability of the battery, reducing the gas utilization, performance and life of the fuel cell, and in serious cases, safety accidents may occur.
[0005] Therefore, the market is in urgent need of a film product with high cohesive strength, high hydrolysis resistance and resistance to cold and hot shocks for bipolar plates and membrane electrode sealing. Summary of the invention
[0006] The first technical problem to be solved by the present invention is: in view of the deficiencies in the prior art, to provide an adhesive composition for fuel cells, which has high cohesive strength, good hydrolysis resistance and good resistance to thermal shock.
[0007] To solve the above-mentioned first technical problem, the technical solution of the present invention is:
[0008] An adhesive composition for a fuel cell, comprising a release layer I, a hot melt adhesive layer I, a hot melt adhesive layer II and a release layer II arranged in sequence;
[0009] The hot melt adhesive layer I is an acid-modified polyolefin resin hot melt adhesive layer, and the hot melt adhesive layer II is a modified polyurethane resin hot melt adhesive layer.
[0010] Preferably, the release layer I and the release layer II are both films coated with a non-silicone resin release material, and the thickness of the release layer I and the release layer II are both 25-150 μm.
[0011] Preferably, the thickness of the hot melt adhesive layer I and the hot melt adhesive layer II are both 20-80 μm.
[0012] Preferably, the acid-modified polyolefin resin hot melt adhesive layer comprises an acid-modified polyolefin resin obtained from a modifier, wherein the modifier is at least one of a free acid anhydride and a substitution product thereof.
[0013] Preferably, the melting point of the acid-modified polyolefin resin is 85-125°C.
[0014] Preferably, the acid-modified polyolefin resin hot melt adhesive layer further comprises a tackifier, a curing agent I and a diluent solvent I, and the weight ratio of the acid-modified polyolefin resin, the tackifier, the curing agent I and the diluent solvent I is in the range of 100: (5-15): (0.1-3): (20-100);
[0015] The curing agent I is any one of an epoxy curing agent and an isocyanate curing agent;
[0016] The dilution solvent I is any one of toluene, xylene, cyclohexane, ethyl acetate, acetone, butanone, and cyclohexanone, or a mixed solution of two or more thereof.
[0017] Preferably, the modified polyurethane resin hot melt adhesive layer is composed of modified polyurethane resin, epoxy resin, curing agent II and diluent solvent II in a weight ratio of 100: (10-50): (0.5-5): (400-700).
[0018] Preferably, the epoxy resin is any one of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, or a mixture of two or more thereof.
[0019] Preferably, the curing agent II is any one of an epoxy curing agent, an isocyanate curing agent, and a carbodiimide curing agent;
[0020] The dilution solvent II is any one of ethyl acetate, acetone, butanone, cyclohexanone, methyl isobutyl ketone, toluene, xylene, and cyclohexane, or a mixed solution of two or more thereof.
[0021] The second technical problem to be solved by the present invention is: in view of the shortcomings of the prior art, a method for preparing an adhesive composition for a fuel cell is provided, wherein the prepared adhesive composition has high cohesive strength, good hydrolysis resistance and good resistance to thermal shock.
[0022] To solve the above second technical problem, the technical solution of the present invention is:
[0023] A method for preparing a fuel cell adhesive composition comprises the following steps:
[0024] S01. Preparation of acid-modified polyolefin resin
[0025] Add polyolefin, toluene, modifier and thermal initiator in a reaction kettle in a mass ratio of 100: (300-500): (5-10): (0.1-2), stir and heat, react at 140-160° C. for 1-3 hours, cool the obtained reaction solution to 40° C. to obtain an acid-modified polyolefin resin, wherein the thermal initiator is any one of dibenzoyl peroxide, azobisisobutyronitrile, di-tert-butyl peroxide or tert-butyl perbenzoate;
[0026] S02. Preparation of modified polyurethane resin
[0027] Add polycarbonate diol to a reaction container, dehydrate for 1 to 3 hours at 110 to 130°C and -0.85 to -0.1 MPa, cool to 70°C, then introduce nitrogen to add diisocyanate to the reaction container, heat to 70 to 80°C after dissolving, and react for 1 to 3 hours to obtain a prepolymer;
[0028] Nitrogen is introduced into the prepared prepolymer, a chain extender with a fixed polyurethane hard segment content of 20-25% w / w is added, and 0.03-0.05% w / w of dibutyltin dilaurate is dripped into the prepolymer, and the prepolymer is stirred rapidly for 8-12 minutes, and the reaction solution is poured out, and the prepolymer is post-cured in an oven at 110-130° C. for 12-36 hours to obtain a hydroxyl-containing modified polyurethane resin;
[0029] S03. Preparation of hot melt adhesive layer
[0030] The acid-modified polyolefin resin prepared in step S01 is added with a tackifier, a curing agent I and a diluting solvent I, and then stirred evenly, filtered through a 200-800 mesh filter or a 1-20 μm filter element, and then coated on a release film using a blade coater or a CED coater, and dried to completely attach the release layer I, thereby obtaining a hot melt adhesive layer I;
[0031] The modified polyurethane resin prepared in step S02 is added with epoxy resin, curing agent II and diluent II in the same manner, and then stirred evenly, filtered, coated, and dried to completely attach release layer II, thereby obtaining hot melt adhesive layer II;
[0032] S04. Preparation of binder composition for fuel cell
[0033] The hot melt adhesive layer I and the side of the hot melt adhesive layer II without the release layer are laminated together by roller pressing at 80°C. After aging, an adhesive composition for fuel cells with double-sided hot melt adhesive layers is obtained.
[0034] Due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0035] 1. The present invention uses a fuel cell adhesive composition product with hot-melt bonding function to simplify the single cell manufacturing process and significantly improve the efficiency and yield.
[0036] 2. The present invention adopts a stacked combination of two types of adhesive films. By bonding the acid-modified polyolefin resin hot-melt adhesive layer to the electrode plate and the modified polyurethane resin hot-melt adhesive layer to the substrate, it can not only effectively bond the electrode plate and the packaged membrane electrode to avoid interlayer peeling, but also fully solve the durability problem of the components in an environment of contact with moisture, thereby improving the service life of the battery stack.
[0037] 3. The present invention uses chemical materials without N, P, S and Al, Cu, Ni, Cd, Cr, Pb, and Fe to make the hot-melt adhesive layer, thereby avoiding the precipitation problem of the hot-melt adhesive film after long-term acid immersion, thereby greatly improving the service life of the single battery.
[0038] 4. The fuel cell adhesive composition prepared by the present invention can be directly assembled with the electrode plate and the membrane electrode after die-cutting, which greatly improves the production efficiency. At the same time, only the adhesive layer is used during the battery packaging process, which effectively reduces the production cost.
[0039] 5. The fuel cell adhesive composition prepared by the present invention has the characteristics of no initial adhesion, high bonding strength, gas barrier and low compression deformation in the early stage of single cell production. During use, it solves the problems of lamination and bubble removal, strong adhesion and peeling strength attenuation under high temperature conditions, greatly improves the efficiency and yield of the single cell packaging process, and is conducive to the industrial development of single cell products. DETAILED DESCRIPTION
[0040] The present invention will be further described below in conjunction with the embodiments. Example 1
[0041] A method for preparing a fuel cell adhesive composition comprises the following steps:
[0042] S01. Preparation of acid-modified polyolefin resin
[0043] Polyolefin, toluene, maleic anhydride and dibenzoyl peroxide were added in a mass ratio of 100:300:5:0.1, heated while stirring, and reacted at 140°C for 1 hour. After the obtained reaction solution was cooled to 40°C, an acid-modified polyolefin resin was obtained with a melting point of 90°C.
[0044] S02. Preparation of modified polyurethane resin
[0045] 50g of polycarbonate diol was added to a reaction container, dehydrated at 110°C and -0.85 to -0.1MPa for 1h, cooled to 70°C, and then nitrogen was introduced. 12.2g of diisocyanate was added to the reaction container, dissolved, heated to 70°C, and reacted for 1h to obtain a prepolymer;
[0046] Nitrogen was introduced into the prepared prepolymer, a chain extender with a fixed polyurethane hard segment content of 20% w / w was added, and 0.03% w / w of dibutyltin dilaurate was dropped into the prepolymer, and the mixture was rapidly stirred for 8 minutes. The reaction solution was poured out and post-cured in an oven at 110° C. for 12 hours to obtain a hydroxyl-containing modified polyurethane resin.
[0047] S03. Preparation of hot melt adhesive layer
[0048] The acid-modified polyolefin resin prepared in step S01, Arizona tackifier NG98, Nan Ya epoxy curing agent NPEL-128 and toluene are mixed evenly in a weight ratio of 100:5:0.1:20, filtered through a 200-mesh filter, and then coated on a release film using a doctor blade coater. After drying, a release layer I with a thickness of 25 μm is attached to obtain a hot melt adhesive layer I with a thickness of 20 μm.
[0049] The modified polyurethane resin prepared in step S02 is mixed with Tiantai Chemical bisphenol A epoxy resin BE186EL, Covestro isocyanate curing agent L75 and ethyl acetate in a weight ratio of 100:10:0.5:400 by the same method, stirred evenly, filtered, coated, and dried to completely attach a release layer II with a thickness of 25 μm, and obtain a hot melt adhesive layer II with a thickness of 20 μm;
[0050] S04. Preparation of binder composition for fuel cell
[0051] The hot melt adhesive layer I and the side of the hot melt adhesive layer II without the release layer are laminated together by roller pressing at 80°C. After aging, an adhesive composition for fuel cells with double-sided hot melt adhesive layers is obtained. Example 2
[0052] A method for preparing a fuel cell adhesive composition comprises the following steps:
[0053] S01. Preparation of acid-modified polyolefin resin
[0054] Add polyolefin, toluene, monomethyl maleate and azobisisobutyronitrile in a mass ratio of 100:400:8:0.5, heat while stirring, react at 150°C for 2h, cool the obtained reaction solution to 40°C, and obtain an acid-modified polyolefin resin with a melting point of 100°C;
[0055] S02. Preparation of modified polyurethane resin
[0056] 50g of polycarbonate diol was added to a reaction container, dehydrated at 120°C and -0.85 to -0.1MPa for 2h, cooled to 70°C, and then nitrogen was introduced. 12.5g of diisocyanate was added to the reaction container, and after dissolving, the temperature was raised to 75°C and reacted for 2h to obtain a prepolymer;
[0057] Nitrogen was introduced into the prepared prepolymer, a chain extender with a fixed polyurethane hard segment content of 23% w / w was added, and 0.04% w / w of dibutyltin dilaurate was dropped into the prepolymer, and the mixture was rapidly stirred for 10 minutes. The reaction solution was poured out and post-cured in an oven at 120° C. for 20 hours to obtain a hydroxyl-containing modified polyurethane resin.
[0058] S03. Preparation of hot melt adhesive layer
[0059] The acid-modified polyolefin resin prepared in step S01, the tackifier Clearon P115 produced by Anyuan Chemical, the isocyanate curing agent Desmodur H produced by Covestro, and the mixed solution of xylene and cyclohexane are uniformly stirred in a weight ratio of 100:10:1:50, filtered through a 600-mesh filter, and then coated on a release film using a CED coater, and dried to completely attach a release layer I with a thickness of 100 μm, thereby obtaining a hot melt adhesive layer I with a thickness of 60 μm, wherein the mass ratio of xylene to cyclohexane is 1:1;
[0060] In the same way, the modified polyurethane resin prepared in step S02, Nan Ya bisphenol F epoxy resin NPEF-170, Covestro isocyanate curing agent Desmodur H and a mixed solution of acetone, butanone and cyclohexanone in a weight ratio of 100:20:2:500 are mixed and stirred evenly, filtered, coated, and dried to completely attach a release layer II with a thickness of 50 μm, thereby obtaining a hot melt adhesive layer II with a thickness of 40 μm, wherein the mass ratio of acetone, butanone and cyclohexanone is 1:2:1;
[0061] S04. Preparation of binder composition for fuel cell
[0062] The hot melt adhesive layer I and the side of the hot melt adhesive layer II without the release layer are laminated together by roller pressing at 80°C. After aging, an adhesive composition for fuel cells with double-sided hot melt adhesive layers is obtained. Example 3
[0063] A method for preparing a fuel cell adhesive composition comprises the following steps:
[0064] S01. Preparation of acid-modified polyolefin resin
[0065] Add polyolefin, toluene, maleic acid and di-tert-butyl peroxide in a mass ratio of 100:500:10:2, heat while stirring, react at 160°C for 3 hours, cool the obtained reaction solution to 40°C, and obtain an acid-modified polyolefin resin with a melting point of 105°C;
[0066] S02. Preparation of modified polyurethane resin
[0067] 50g of polycarbonate diol was added to a reaction container, dehydrated at 130°C and -0.85 to -0.1MPa for 3h, cooled to 70°C, and then nitrogen was introduced. 12.7g of diisocyanate was added to the reaction container, and after dissolving, the temperature was raised to 80°C and reacted for 3h to obtain a prepolymer;
[0068] Nitrogen was introduced into the prepared prepolymer, a chain extender with a fixed polyurethane hard segment content of 25% w / w was added, and 0.05% w / w of dibutyltin dilaurate was dropped into the prepolymer, and the mixture was rapidly stirred for 12 minutes. The reaction solution was poured out and post-cured in an oven at 130° C. for 36 hours to obtain a hydroxyl-containing modified polyurethane resin.
[0069] S03. Preparation of hot melt adhesive layer
[0070] The acid-modified polyolefin resin prepared in step S01, Arakawa Chemical tackifier Arcon M100, Nan Ya epoxy curing agent NPEL-128 and a mixed solution of ethyl acetate, acetone, butanone and cyclohexanone in a weight ratio of 100:15:3:100 were stirred evenly, filtered through an 800-mesh filter, and then coated on a release film using a doctor blade coater, and dried to completely attach a release layer I with a thickness of 150 μm, thereby obtaining a hot melt adhesive layer I with a thickness of 80 μm;
[0071] The modified polyurethane resin prepared in step S02 is mixed with Jinan Huakai bisphenol S epoxy resin S-28, Starr carbodiimide curing agent Permuthane® XR-5580 and a mixed solution of methyl isobutyl ketone and toluene in a weight ratio of 100:50:5:700 by the same method, stirred evenly, filtered, coated, and dried to completely attach a release layer II with a thickness of 150 μm, and obtain a hot melt adhesive layer II with a thickness of 80 μm, wherein the mass ratio of methyl isobutyl ketone to toluene is 2:1;
[0072] S04. Preparation of binder composition for fuel cell
[0073] The hot melt adhesive layer I and the side of the hot melt adhesive layer II without the release layer are laminated together by roller pressing at 80°C. After aging, an adhesive composition for fuel cells with double-sided hot melt adhesive layers is obtained. Example 4
[0074] A method for preparing a fuel cell adhesive composition comprises the following steps:
[0075] S01. Preparation of acid-modified polyolefin resin
[0076] Add polyolefin, toluene, acrylate, and tert-butyl perbenzoate in a mass ratio of 100:400:10:1.5, heat while stirring, and react at 150°C for 2.5 hours. After cooling the obtained reaction solution to 40°C, an acid-modified polyolefin resin with a melting point of 120°C is obtained;
[0077] S02. Preparation of modified polyurethane resin
[0078] 50g of polycarbonate diol was added to a reaction container, dehydrated at 125°C and -0.85 to -0.1MPa for 2.5h, cooled to 70°C, and then nitrogen was introduced. 12.9g of diisocyanate was added to the reaction container, and after dissolving, the temperature was raised to 76°C and reacted for 2.5h to obtain a prepolymer;
[0079] Nitrogen was introduced into the prepared prepolymer, a chain extender with a fixed polyurethane hard segment content of 22% w / w was added, and 0.04% w / w of dibutyltin dilaurate was dropped into the prepolymer, and the mixture was rapidly stirred for 11 minutes, and the reaction solution was poured out and post-cured in an oven at 125° C. for 30 hours to obtain a hydroxyl-containing modified polyurethane resin.
[0080] S03. Preparation of hot melt adhesive layer
[0081] The acid-modified polyolefin resin prepared in step S01, Eastman tackifier Regalite S5100, DIC epoxy curing agent EPICLON HP-4710 and a mixed solution of diluent I toluene and butanone in a weight ratio of 100:12:2.5:70 were stirred evenly, filtered through a 1 μm filter element, and then coated on a release film using a CED coater, and dried to completely attach a release layer I with a thickness of 80 μm, thereby obtaining a hot melt adhesive layer I with a thickness of 55 μm;
[0082] The modified polyurethane resin obtained in step S02 is mixed with a mixture of bisphenol A epoxy resin and bisphenol S epoxy resin, Covestro isocyanate curing agent N3300 and a mixed solution of xylene and cyclohexane in a weight ratio of 100:15:2.5:600 by the same method, stirred evenly, filtered, coated, and dried to completely attach a release layer II with a thickness of 120 μm, and obtain a hot melt adhesive layer II with a thickness of 30 μm, wherein the mass ratio of bisphenol A epoxy resin to bisphenol S epoxy resin is 1:1, and the mass ratio of xylene to cyclohexane is 1:3;
[0083] S04. Preparation of binder composition for fuel cell
[0084] The hot melt adhesive layer I and the side of the hot melt adhesive layer II without the release layer are laminated together by roller pressing at 80°C. After aging, an adhesive composition for fuel cells with double-sided hot melt adhesive layers is obtained. Example 5
[0085] A method for preparing a fuel cell adhesive composition comprises the following steps:
[0086] S01. Preparation of acid-modified polyolefin resin
[0087] Add polyolefin, toluene, methacrylic acid and dibenzoyl peroxide in a mass ratio of 100:300:8:0.5, heat while stirring, react at 140°C for 3 hours, cool the obtained reaction solution to 40°C, and obtain an acid-modified polyolefin resin with a melting point of 115°C;
[0088] S02. Preparation of modified polyurethane resin
[0089] 50g of polycarbonate diol was added to a reaction container, dehydrated at 110°C and -0.85 to -0.1MPa for 2h, cooled to 70°C, and then nitrogen was introduced. 13.1g of diisocyanate was added to the reaction container, and after dissolving, the temperature was raised to 75°C and reacted for 1h to obtain a prepolymer;
[0090] Nitrogen was introduced into the prepared prepolymer, a chain extender with a fixed polyurethane hard segment content of 20% w / w was added, and 0.03% w / w of dibutyltin dilaurate was dropped into the prepolymer, and the mixture was rapidly stirred for 12 minutes. The reaction solution was poured out and post-cured in an oven at 130° C. for 18 hours to obtain a hydroxyl-containing modified polyurethane resin.
[0091] S03. Preparation of hot melt adhesive layer
[0092] The acid-modified polyolefin resin prepared in step S01, Eastotac C100R, Covestro isocyanate curing agent N3300 and ethyl acetate are mixed evenly in a weight ratio of 100:8:1:30, filtered through a 400-mesh filter, and then coated on a release film using a doctor blade coater, and dried to completely attach a release layer I with a thickness of 50 μm, thereby obtaining a hot melt adhesive layer I with a thickness of 50 μm;
[0093] The modified polyurethane resin prepared in step S02 is mixed with Phoenix brand bisphenol A epoxy resin E44, Covestro isocyanate curing agent N3300 and cyclohexane in a weight ratio of 100:15:3:550 by the same method, stirred evenly, filtered, coated, and dried to completely attach a release layer II with a thickness of 60 μm, thereby obtaining a hot melt adhesive layer II with a thickness of 60 μm;
[0094] S04. Preparation of binder composition for fuel cell
[0095] The hot melt adhesive layer I and the side of the hot melt adhesive layer II without the release layer are laminated together by roller pressing at 80°C. After aging, an adhesive composition for fuel cells with double-sided hot melt adhesive layers is obtained.
[0096] The product performance of the fuel cell binder composition in the above Examples 1-5 was tested respectively. The specific test items and test methods are shown in Table 1 below, and the test results are shown in Table 2.
[0097] Table 1
[0098]
[0099] Table 2
[0100]
[0101] It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope limited by the appended claims of the application.
Claims
1. A fuel cell adhesive composition, characterized in that: It includes a release layer I, a hot melt adhesive layer I, a hot melt adhesive layer II and a release layer II which are arranged in sequence; The hot melt adhesive layer I is an acid-modified polyolefin resin hot melt adhesive layer, and the hot melt adhesive layer II is a modified polyurethane resin hot melt adhesive layer; The method for preparing the fuel cell adhesive composition comprises the following steps: S01. Preparation of acid-modified polyolefin resin Add polyolefin, toluene, modifier and thermal initiator in a reaction kettle in a mass ratio of 100: (300-500): (5-10): (0.1-2), stir and heat, react at 140-160° C. for 1-3 hours, cool the obtained reaction solution to 40° C. to obtain an acid-modified polyolefin resin, wherein the thermal initiator is any one of dibenzoyl peroxide, azobisisobutyronitrile, di-tert-butyl peroxide or tert-butyl perbenzoate; S02. Preparation of modified polyurethane resin Add polycarbonate diol to a reaction container, dehydrate for 1 to 3 hours at 110 to 130°C and -0.85 to -0.1 MPa, cool to 70°C, then introduce nitrogen to add diisocyanate to the reaction container, heat to 70 to 80°C after dissolving, and react for 1 to 3 hours to obtain a prepolymer; Nitrogen is introduced into the prepared prepolymer, a chain extender with a fixed polyurethane hard segment content of 20-25% w / w is added, and 0.03-0.05% w / w of dibutyltin dilaurate is dripped into the prepolymer, and the prepolymer is stirred rapidly for 8-12 minutes, and the reaction solution is poured out, and the prepolymer is post-cured in an oven at 110-130° C. for 12-36 hours to obtain a hydroxyl-containing modified polyurethane resin; S03. Preparation of hot melt adhesive layer The acid-modified polyolefin resin prepared in step S01 is added with a tackifier, a curing agent I and a diluting solvent I, and then stirred evenly, filtered through a 200-800 mesh filter or a 1-20 μm filter element, and then coated on a release film using a blade coater or a CED coater, and dried to completely attach the release layer I, thereby obtaining a hot melt adhesive layer I; The modified polyurethane resin prepared in step S02 is added with epoxy resin, curing agent II and diluent II in the same manner, and then stirred evenly, filtered, coated, and dried to completely attach release layer II, thereby obtaining hot melt adhesive layer II; S04. Preparation of adhesive composition for fuel cell The hot melt adhesive layer I and the side of the hot melt adhesive layer II without the release layer are laminated together by roller pressing at 80°C. After aging, an adhesive composition for fuel cells with double-sided hot melt adhesive layers is obtained.
2. The fuel cell binder composition according to claim 1, wherein: The release layer I and the release layer II are both films coated with non-silicone resin release materials, and the thickness of the release layer I and the release layer II are both 25-150 μm.
3. The fuel cell binder composition according to claim 1, wherein: The thickness of the hot melt adhesive layer I and the hot melt adhesive layer II are both 20-80 μm.
4. The fuel cell binder composition according to claim 1, wherein: The acid-modified polyolefin resin hot melt adhesive layer comprises an acid-modified polyolefin resin obtained from a modifier, wherein the modifier is at least one of a free acid anhydride and a substitution product thereof.
5. The fuel cell binder composition according to claim 4, wherein: The melting point of the acid-modified polyolefin resin is 80-125°C.
6. The fuel cell binder composition according to claim 4, wherein: The acid-modified polyolefin resin hot melt adhesive layer further comprises a tackifier, a curing agent I and a diluting solvent I, wherein the weight ratio of the acid-modified polyolefin resin, the tackifier, the curing agent I and the diluting solvent I is 100: (5-15): (0.1-3): (20-100); The curing agent I is any one of an epoxy curing agent and an isocyanate curing agent; The dilution solvent I is any one of toluene, xylene, cyclohexane, ethyl acetate, acetone, butanone, and cyclohexanone, or a mixed solution of two or more thereof.
7. The fuel cell binder composition according to claim 1, wherein: The modified polyurethane resin hot melt adhesive layer is composed of modified polyurethane resin, epoxy resin, curing agent II and diluent solvent II in a weight ratio of 100: (10-50): (0.5-5): (400-700).
8. The fuel cell binder composition according to claim 7, wherein: The epoxy resin is any one of bisphenol A epoxy resin, bisphenol F epoxy resin, and bisphenol S epoxy resin, or a mixture of two or more thereof.
9. The fuel cell binder composition according to claim 7, wherein: The curing agent II is any one of an epoxy curing agent, an isocyanate curing agent, and a carbodiimide curing agent; The dilution solvent II is any one of ethyl acetate, acetone, butanone, cyclohexanone, methyl isobutyl ketone, toluene, xylene, and cyclohexane, or a mixed solution of two or more thereof.
Citation Information
Patent Citations
Composite release film as well as preparation method and application thereof
CN117659894A
Hot melt adhesive film for single battery and preparation method of hot melt adhesive film
CN118562401A
Cited By
Monocell packaging structure and preparation method thereof
CN121642014A
A single cell packaging structure and a method for manufacturing the same
CN121642014B